2020
DOI: 10.3390/ijms21197388
|View full text |Cite
|
Sign up to set email alerts
|

Is the Secret of VDAC Isoforms in Their Gene Regulation? Characterization of Human VDAC Genes Expression Profile, Promoter Activity, and Transcriptional Regulators

Abstract: VDACs (voltage-dependent anion-selective channels) are pore-forming proteins of the outer mitochondrial membrane, whose permeability is primarily due to VDACs’ presence. In higher eukaryotes, three isoforms are raised during the evolution: they have the same exon–intron organization, and the proteins show the same channel-forming activity. We provide a comprehensive analysis of the three human VDAC genes (VDAC1–3), their expression profiles, promoter activity, and potential transcriptional regulators. VDAC iso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 81 publications
(100 reference statements)
2
25
0
Order By: Relevance
“…The level of the VDAC1 and VDAC2 transcripts is comparable, while VDAC3 is lower than the other two isoforms, confirming previous experimental conclusions drawn by RT-PCR [ 59 ]. While confirming that VDAC isoforms are ubiquitously expressed, the comparison with the data present in a second repository (RNA-seq CAGE RIKEN FANTOM 5’ project) [ 60 ] of Expression Atlas repository of EMBL-EBI [ 61 ] revealed that the VDAC3 expression levels were higher than VDAC2 and VDAC1, whose transcripts are scarcely represented in all tissues [ 57 ]. The data emerging from this analysis highlight for the first time the prevalence of VDAC3 gene transcription as compared to other isoforms reflecting a higher promoter activity.…”
Section: Vdac Isoforms Genes Expression Regulation: the Key To Undmentioning
confidence: 84%
See 4 more Smart Citations
“…The level of the VDAC1 and VDAC2 transcripts is comparable, while VDAC3 is lower than the other two isoforms, confirming previous experimental conclusions drawn by RT-PCR [ 59 ]. While confirming that VDAC isoforms are ubiquitously expressed, the comparison with the data present in a second repository (RNA-seq CAGE RIKEN FANTOM 5’ project) [ 60 ] of Expression Atlas repository of EMBL-EBI [ 61 ] revealed that the VDAC3 expression levels were higher than VDAC2 and VDAC1, whose transcripts are scarcely represented in all tissues [ 57 ]. The data emerging from this analysis highlight for the first time the prevalence of VDAC3 gene transcription as compared to other isoforms reflecting a higher promoter activity.…”
Section: Vdac Isoforms Genes Expression Regulation: the Key To Undmentioning
confidence: 84%
“…The studies of the structure, activity, and regulation of VDAC genes aim at obtaining a reliable picture of their differences in tissue expression or sensitivity to specific stimuli [ 57 ]. In humans, for each VDAC gene, several different transcript splice variants were identified: they did not vary in the coding region but mainly in the length of their 5′-UTR and 3′-UTR.…”
Section: Vdac Isoforms Genes Expression Regulation: the Key To Undmentioning
confidence: 99%
See 3 more Smart Citations